Psychological well being of families of people living with HIV/AIDS (PLWHA) - Anugrah, Mita Majdina; Nuryani, Reni; Lindasari, Sri Wulan (Alma Ata University Press, 2025)
Background: HIV/AIDS is a terminal disease that remains the leading cause of death worldwide, including in Indonesia. This disease has a wide impact, not only for sufferers but also for their social environment. Caregivers of people living with HIV/AIDS (PLWHA) often experience psychological distress, especially when they are not prepared to care for sick family members. Their ability to fulfill the five family duties in health is greatly influenced by their psychological well being. Objectives: This study aims to describe the psychological well-being of caregivers of people living with HIV/AIDS (PLWHA) in Sumedang regency.Methods: The method used in this research is descriptive quantitative. The sample in this study amounted to 196 respondents selected by simple random sampling technique. The instrument used was the Ryff Psychological Well-Being Scale, which has a validity range of 0.279 to 0.660 and a reliability score (Cronbach's Alpha) of 0.885.Results: The results of the study showed that most caregivers (52.1%) were in the moderate psychological well-being category, while 47.9% were in the high category. Among the six dimensions of psychological well-being that were studied in this study, only purpose in life and personal growth were predominantly in the high category (50-60%). The demographic analysis revealed that most respondents were aged 20–55 years (M = 36.3, SD = 10.9), the majority were female (56.1%), and most worked as housewives (44.8%). The duration of caregiving was predominantly 1–5 years (61.7%; M = 2.7, SD = 2.5).Conclusions: It can be concluded that most caregivers of People Living with HIV/AIDS (PLWHA) exhibit moderate levels of psychological well-being. This indicates that caregivers can generally accept their strengths and weaknesses, build positive relationships, adapt to their environment, set clear life goals, demonstrate independence, and engage in personal growth. Therefore, it is necessary to enhance family counseling programs within supportive care and treatment services, as well as strengthen family psychoeducation initiatives in nursing and healthcare institutions